(Nl@CIAN pRIGOVINs (NmONOGRAFI^ESKIJ O^ERKs - (Ne(B.(NrU^_EWSKAQs ((NmOSKWAs (NlENINGRADs (NkOMPOZITORs, 1977)
(N|TA KNIGA POSWQ]ENA TWOR^ESTWU LENINGRADSKOGO KOMPOZITORA l@CIANA aBRAMOWI^A pRIGOVINA AWTORA ORATORIJ SIMFONIJ MNOGO^ISLENNYH KAMERNYH PROIZWEDENIJ(B.s
Keywords: (NMONOGRAFIQs